Interaction of monolignols and their related phenols with cellulose triacetate in various states - Nobuhiro Shimoda; Yoshikuni Teramoto; Toshiyuki Takano (Journal of Wood Science)
Abstract The present study comprises an investigation of the interactions of monolignols and their related phenols, such as catechol and vanillin (both are collectively referred to as “ML-phenols” herein), with cellulose triacetate (CTA) in solution, solid, and solution/solid states. The objective was to collect the basic knowledge for the role of hemicellulose with acetyl groups in the polymerization of monolignols and for lignin/cellulose acetate composites. The ML-phenols interacted with CTA through their hydroxyl groups in a ML-phenols/CTA ratio of 1/1 (w/w) in CDCl3 (solution state). They also interacted with CTA through their hydroxy groups in addition to hydrophobic interactions in a ML-phenols/CTA ratio of 1/1 (w/w) in cast films (solid state). Especially, the monolignols were incorporated as amorphous in the CTA films, even at high content, suggesting that they had high affinity for CTA. The dynamic adsorption of ML-phenols onto the CTA film was investigated by quartz crystal microbalance with dissipation monitoring (QCM-D). All the ML-phenols were adsorbed onto the CTA-coated QCM-D Au sensor in the system (ML-phenols/CTA: solution/solid state), and the methoxy groups of the ML-phenols promoted the adsorption onto the CTA. Further investigation into the adsorption of monolignols has been conducted. All monolignols were adsorbed onto the CTA-coated QCM-D Au sensor, whereas they were not entirely adsorbed onto the cellulose-coated QCM-D Au sensor in the system, suggesting that the acetyl groups of hemicellulose are adsorption points for monolignols during lignin formation and the hydrophobic interactions through the methoxy groups might be one of the important factors for the adsorption.